MORPHOLOGICAL CHANGES IN CARDIAC TISSUE AFTER MECHANICAL TRAUMA UNDER GENERAL ANESTHESIA: AN EXPERIMENTAL ANALYSIS - Vohidov Bekzod Rafiq o’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This experimental study investigated morphological changes in rat heart tissue subjected to mechanical trauma under general anesthesia (nitrous oxide – N₂O). According to histological analysis, dystrophic changes in cardiomyocytes, karyolysis, cytolysis, focal necrosis, interstitial edema, venous congestion, and leukocytic infiltration were identified. These structural changes may impair cardiac function and are essential indicators for evaluating the effects of anesthesia. The study results are significant for early detection and prevention of cardiac complications in clinical practice.